2019
DOI: 10.2147/cia.s220890
|View full text |Cite
|
Sign up to set email alerts
|

<p>Balance training using virtual reality improves balance and physical performance in older adults at high risk of falls</p>

Abstract: PurposeExercise programs designed for falls prevention have been proven effective in reducing falls by approximately 21%. Virtual reality may provide a viable alternative intervention for falls prevention. This study compared the effects of virtual reality training using the Balance Rehabilitation Unit (BRU) versus exercise using a modified Otago Exercise Programme (EX) on improving balance and physical performance in the short-term restorative care setting of the Gait and Balance Gym (Gabagym).Patients and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 28 publications
1
69
3
4
Order By: Relevance
“…Additionally, VR games can be used as an affordable tool for home exercise in older adults [ 11 , 13 ]. VR games are mostly used in restoring body balance and gait functions [ 11 , 14 ] and, less often, to improve other functions, such as muscle strength [ 11 ]. Despite promising effects, the quality of scientific evidence supporting the use of VR is insufficient to recommend using it in everyday rehabilitation routines, especially in patients with orthopedic conditions or dysfunctions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, VR games can be used as an affordable tool for home exercise in older adults [ 11 , 13 ]. VR games are mostly used in restoring body balance and gait functions [ 11 , 14 ] and, less often, to improve other functions, such as muscle strength [ 11 ]. Despite promising effects, the quality of scientific evidence supporting the use of VR is insufficient to recommend using it in everyday rehabilitation routines, especially in patients with orthopedic conditions or dysfunctions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent reviews and meta-analyses revealed that new technologies (eg, virtual reality [VR], augmented reality, exergames, and artificial intelligence) have opened the door to a new generation of intervention programs designed to prevent the occurrence of falls [ 6 - 8 ]. Recent studies also demonstrated the effectiveness of training programs implemented via new technologies for improving the control mechanisms involved in balance [ 9 , 10 ] and goal-directed locomotion [ 11 , 12 ] in older adults. For instance, specific exergames have been designed to train balance control, focusing on either the static control of the center of mass or its control while performing precise, rapid, and well-directed steps in balance-threatening situations [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, acceptance before a first use of a VRH designed to reduce older adults’ risk of falling through their use in intervention programs has not yet been studied. The fact that the positive influence on fall prevention of training programs using VRHs has been validated [ 10 ] reinforces the relevance of studying acceptance of such a VRH. Indeed, older adults who have a low acceptance score also have a very high probability of never adopting this kind of VRH despite its objective usefulness to maintain and improve their functional capacities, but this hypothesis has not yet been tested.…”
Section: Introductionmentioning
confidence: 99%
“…The participants were also informed that they could leave the study at any time without any explanation. The results of previous studies [21][22][23][24][25] indicate that posturographic variables in static and dynamic tests in healthy elderly people remain stable over time (6,9,12, or 14 weeks). Hence, based on results previously published in the literature, we decided not to include the control group in our preliminary research.…”
Section: Participantsmentioning
confidence: 99%